Climate change-induced conflicts in rural Nigeria: Experience from herder-arable crop farmers in selected rural communities of Ekiti State - Oluwatayo, Isaac Busayo; Ojo, Olaniyi Oluwatosin (Asian Journal of Agriculture and Rural Development, 2025)
The problem of climate change is multidimensional, especially in countries where the capacity to cope with shocks is limited. This is further aggravated by socioeconomic conditions, limited buffer stock and insurance, poor credit markets, and an unstable macroeconomic environment. While arable crop farmers in rural Nigeria thrive on proceeds from farming activities, the incessant herder-arable crop farmer conflict exacerbated by climate change has brought untold hardship to these farmers. The study examined determinants of herder-arable crop farmer conflicts in selected rural communities of Ekiti State, Nigeria. Data were collected from a random sample of 220 smallholder farmers via a multistage random sampling technique. Analytical tools employed include descriptive statistics and a probit regression model. A descriptive analysis of respondents’ socioeconomic characteristics revealed their average age and household size to be 56 years and 4 members, respectively. Respondents’ distribution by educational level showed that one-third of them (68.5%) had less than secondary education, with 73.2% having no access to credit. Herder-arable crop farmer conflict determinants include age, years of schooling, farming experience, credit access, planting time, extension contacts, and farm location, among others. The findings have implications for food security, employment, investment drive, rural-urban drift, and security in the study area.